2021
DOI: 10.1002/adem.202101199
|View full text |Cite
|
Sign up to set email alerts
|

On the Formation Mechanism of Banded Microstructures in Electron Beam Melted Ti–48Al–2Cr–2Nb and the Design of Heat Treatments as Remedial Action

Abstract: The formation mechanism of banded microstructures of an electron beam melted engineering intermetallic Ti–48Al–2Cr–2Nb alloy, the solidification behavior, and the heat treatment response are investigated via a process parameter study. Scanning electron microscopy, hardness testing, X‐ray diffraction, electron probe microanalysis, thermomechanical analysis, electron backscatter diffraction, heat treatments, as well as thermodynamic equilibrium calculation, and numerical simulation were performed. All specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 87 publications
1
26
0
Order By: Relevance
“…In a study on PBF-EB/M of Ti-48Al-2Cr-2Nb, Wartbichler et al found that a higher energy input during processing increased aluminum evaporation, which in turn had a strong influence on phase composition and phase morphology after heat treatment in the (α þ γ)-phase field. [25] Wimler et al observed a similar effect after annealing of PBF-EB/Mmanufactured Ti-44.8Al-4.1Nb-0.7W-1.1Zr-0.4Si-0.5C-0.1B slightly below the γ-solvus temperature. [27] Previous studies investigated the mechanical properties of PBF-EB/M-manufactured TNM-B1 in tensile tests for vertically manufactured specimens [29] and in tensile and fatigue tests for horizontally manufactured specimens [30] for different test temperatures up to 850 °C, respectively.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…In a study on PBF-EB/M of Ti-48Al-2Cr-2Nb, Wartbichler et al found that a higher energy input during processing increased aluminum evaporation, which in turn had a strong influence on phase composition and phase morphology after heat treatment in the (α þ γ)-phase field. [25] Wimler et al observed a similar effect after annealing of PBF-EB/Mmanufactured Ti-44.8Al-4.1Nb-0.7W-1.1Zr-0.4Si-0.5C-0.1B slightly below the γ-solvus temperature. [27] Previous studies investigated the mechanical properties of PBF-EB/M-manufactured TNM-B1 in tensile tests for vertically manufactured specimens [29] and in tensile and fatigue tests for horizontally manufactured specimens [30] for different test temperatures up to 850 °C, respectively.…”
Section: Introductionmentioning
confidence: 72%
“…In a study on PBF‐EB/M of Ti–48Al–2Cr–2Nb, Wartbichler et al found that a higher energy input during processing increased aluminum evaporation, which in turn had a strong influence on phase composition and phase morphology after heat treatment in the (α + γ)‐phase field. [ 25 ] Wimler et al observed a similar effect after annealing of PBF‐EB/M‐manufactured Ti–44.8Al–4.1Nb–0.7W–1.1Zr–0.4Si–0.5C–0.1B slightly below the γ‐solvus temperature. [ 27 ]…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…[40] It can be noticed that VED-32 exhibits a larger colony size than the other two specimens, presumably because grain growth during heat treatment was not impeded by a second phase. [13] Taking both the DSC results and the cross-sectional images in Figure 6 into account, it seems reasonable to assume that in the case of VED-32, the solution heat treatment temperature of 1290 °C lay above the γ-solvus temperature. For VED-14 and VED-21, however, the same temperature apparently corresponded to a heat treatment in the (α þ γ)-phase field.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] As a consequence, inhomogeneous microstructures and aluminum distribution can occur after PBF-EB/M processing, which may also affect phase transition temperatures and microstructure evolution during heat treatment. [13,14] Apart from unintentional microstructural variations, these evaporation effects can be used on purpose for microstructural design, e.g., to locally adapt the microstructure and manufacture functionally graded materials (FGMs). [15,16] FGMs are characterized by a spatial variation of chemical composition or microstructure, thereby enabling local control of, e.g., the mechanical properties in different areas of the same component according to the specific requirements.…”
Section: Introductionmentioning
confidence: 99%